1998
DOI: 10.5271/sjweh.371
|View full text |Cite
|
Sign up to set email alerts
|

Paternal exposure to pesticides and congenital malformations

Abstract: Garcia AM, Benavides FG, Fletcher T, Orts E. Paternal exposure to pesticides and congenital malformations Scand J Work Environ Health 1998;24(6):473-480.Objectives A case-referent study with 261 matched pairs was carried out in 8 hospitals of Comunidad Valenciana, Spain, to assess the relation between occupatioilal cxposure to pesticides and selccted congenital malfor~nations. In this paper, the rcsults concerning patcnlal exposure are presented. MethodsThe parents of the case patients and the referents were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 35 publications
(29 reference statements)
1
22
0
Order By: Relevance
“…No congenital malformations were reported in the offspring of workers occupationally exposed to pesticides. Results of epidemiologic studies did not provide sufficient evidence to associate exposure to pesticides in mothers with congenital defects in children (García et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…No congenital malformations were reported in the offspring of workers occupationally exposed to pesticides. Results of epidemiologic studies did not provide sufficient evidence to associate exposure to pesticides in mothers with congenital defects in children (García et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A non-hormonal mechanism has been implicated in altering sex-linked reproductive and non-reproductive organs and in affecting the development of the central nervous system (Gray and Ostby 1998). Mothers who were involved in agricultural activities prior to conception or during the first trimester of their pregnancy have an increased risk of nervous system defects, oral clefts or multiple anomalies (Garcia et al 1999). Fathers involved in agriculture have also been reported to have an increased risk of offspring with defects of the nervous and musculoskeletal systems (Garcia et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a number of epidemiologic studies have identified possible associations of parental occupational exposures with birth defects (Cordier et al, 1997;Correa-Villaseñ or et al, 1991Garcia et al, 1998;Khattak et al, 1999;Matte et al, 1993;McMartin et al, 1998;Olshan et al, 1991;Schnitzer et al, 1995;Shaw et al, 1999a,b;Tikkanen and Heinonen, 1992). However, because assessment of parental occupational exposures in these studies was based either on reported industry and job title, which lack information on specific exposures, or on self-reports of exposures to specific agents, which suffer from low sensitivity and potential recall bias (Garcia, 1998;Bauer et al, 1999), it is likely that the exposure groups evaluated included some misclassified subjects and that the observed odds ratios were biased and imprecise.…”
Section: Introductionmentioning
confidence: 99%